Optical properties and electron/nuclear dynamics of nanoparticles - Pandeya, Pratima (Kansas State University, 2021)
Studies of the excited state properties of nanoparticles are extremely important to find a good candidate for applications in the fields of catalysis, solar energy, biomedicine and so on. After absorption of light and excitation of electrons to excited states, the excited electrons can relax to the ground state through radiative and/or non-radiative pathways. We need to understand both the radiative and non-radiative relaxation times and mechanisms to choose the right candidate for different applications. For example, for a nanoparticle to be used as a photosensitizer, electrons should remain in excited states for a long time. In this dissertation, we first study the radiative and non-radiative relaxation mechanisms of excited electrons in thiolate-protected nanoclusters. We also investigate the effect of interparticle separations in tuning the optical properties of plasmonic nanowire assemblies. Finally, we examine the possibility of dinitrogen dissociation upon excitation of plasmonic resonances of single nanoparticles and nanoparticle assemblies. We studied the non-radiative relaxation of excited electrons in [Au₂₅₋ₙAgₙ(SH)₁₈]⁻¹ (n = 1, 12, 25) and Au₂₀(SCH₃)₁₆ using the fewest switches surface hopping approach. In all of the clusters, the electron relaxation from the first excited state (HOMO → LUMO) is found to have the longest decay time compared to the relaxation from higher excited states. This is because of the large gap (HOMO-LUMO gap) compared to the gap present between higher excited states. In the higher excited states, the orbitals are close in energy. So, the excited state population can immediately relax to the nearby orbitals and hence causes the fast relaxation of the excited state population. Among the silver doped Au₂₅ clusters, [Au₁₃Ag₁₂(SH)₁₈]⁻¹ has the fastest decay times and the slowest ground state growth times (i.e. times for the population in an excited state to relax to the ground state) because of the closer lying orbitals in this nanocluster than in other nanoclusters. This suggest that [Au₁₃Ag₁₂(SH)₁₈]⁻¹ is the best candidate to be used as a solar cell photosensitizer compared to other studied clusters. Study of radiative relaxation of excited electrons in Au₂₀(SCH₃)₁₆ shows that luminescence can potentially occur from the S₁, S₂, and S₆ states. Dual luminescence is observed from S₁ at 0.41 eV and 0.68 eV. Without considering the underestimation due to the use of GGA functionals in our calculations, the experimentally observed luminescence at 1.51 eV matches with the S₆ luminescence at 1.50 eV. However, on considering the underestimation, this emission energy is higher than the experimental emission. On adding the underestimation, the S₂ emission at 1.44 eV is also close to the experimental emission at 1.51 eV. The cluster structure (mainly the ring and the trimeric staple motif) become the most distorted in the first excited state with luminescence at 0.41 eV whereas the cluster structure does not distort significantly in the S₂ and S₆ states. We also studied the evolution of absorption spectra of plasmonic nanowire dimers and trimers at interparticle separations of 0.4-2.0 nm. We observed the appearance of an extra peak between the longitudinal and transverse peak when the interparticle separation is 0.6 nm and less. The extra peak was found to have charge transfer character where there is tunneling of electrons from one monomer to another. Finally, we used real-time time dependent density functional methods to investigate the plasmon-mediated dinitrogen dissociation upon activation of plasmon resonances of the icosahedral Al₁₃N₂⁻¹ nanocluster and silver nanowire dimers. Because the occupation of nitrogen antibonding orbitals can lead to dinitrogen dissociation, we examined the occupation of virtual orbitals in Al₁₃N₂⁻¹. We observed the highest possibility of occupation of nitrogen antibonding orbitals by using off-resonant 0.01 au electric fields rather than by using 0.001 au resonant fields. For the parallel, end-to-end and hotspot oriented silver nanowire dimers, we analyzed the N-N distance during the simulation using the Ehrenfest approach. The highest possibility of dinitrogen dissociation was observed using end-to-end oriented nanowires. The dissociation is more likely at small interparticle separation between the monomers compared to larger separation.
Keywords: Nonadiabatic dynamics; Excited state properties; Radiative and nonradiative emission; Nanoclusters and nanowires; Time-dependent density functional theory